The aesthetics of nostalgia : historical representation in Old English verse - Trilling, Renée R. (Toronto Anglo-Saxon series., 2009)
Aesthetics of Nostalgia reads Anglo-Saxon historical verse in terms of how its aesthetic form interacted with the culture and politics of the period.